The effect of accrual-based and real-based earnings management on carbon emission disclosure - Maretha, Lavadhea Shafa; Ginting, Josep (President University Press, 2025)
Amid increasing global attention to sustainability, carbon emission disclosure (CED) has emerged as a critical mechanism for enhancing corporate accountability. Yet, the reliability of CED can be undermined by earnings management practices that mask firms’ true performance. This study examines the influence of accrual-based and real-based earnings management that have the proxies as abnormal cash flows, production costs, and discretionary expenses on CED. Using panel data from energy, basic materials, transportation, and agriculture firms listed on the Indonesia Stock Exchange (IDX) over the 2019–2023 period, the results reveal heterogeneous effects: abnormal cash flows and overproduction significantly reduce the extent of CED, whereas lower discretionary expenses are associated with greater disclosure. These findings advance the literature by illustrating how distinct earnings management strategies differentially shape corporate environmental transparency. Despite inherent limitations in measurement and market scope, the study contributes to sustainability reporting research in emerging markets and offers practical insights for regulators and stakeholders aiming to strengthen the credibility of environmental disclosures.